(untitled) (Journal of the College of Basic Education, 2025)
The study addressed the spatial analysis of land slopes in the Rania region. This study is considered an important geomorphological study, especially given the mountainous nature of the region. The study utilized a digital elevation model (DEM), which is considered one of the best graphic tools used in land slope analysis. The importance of studying slopes stems from the impact of these slopes on various geomorphological processes, particularly the intensity of surface runoff and the extent of its investment in economic activities in the study area. The results of slope analysis using several classifications revealed significant variation between these classifications, with the variance outputs providing a clear and comprehensive understanding of the study area.